2020
DOI: 10.1016/j.breast.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Do YOU know the Ki-67 index of your breast cancer patients? Knowledge of your institution’s Ki-67 index distribution and its robustness is essential for decision-making in early breast cancer

Abstract: Objectives The proliferative activity of the Ki-67 index is important in decision-making of adjuvant treatments in early breast cancer. Its reliability can be reduced by inter-observer variability. This analysis’ objective is to evaluate the robustness of Ki-67 values within one center over 5 years and to compare its distribution with a published dataset. Materials and methods Ki-67 indices of early breast cancers treated at St. Gallen Breast Center were collected (2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…Differential expression of Ki-67 among breast cancer molecular subtypes was previously investigated in different studies, where high expression level among cases of TNBC subtype was reported [ 42 46 ]. Moreover, our result that show a significantly higher Ki-67 expression levels among cases of high grade (grade III) is in accordance with the results of previous studies [ 42 , 43 , 45 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…Differential expression of Ki-67 among breast cancer molecular subtypes was previously investigated in different studies, where high expression level among cases of TNBC subtype was reported [ 42 46 ]. Moreover, our result that show a significantly higher Ki-67 expression levels among cases of high grade (grade III) is in accordance with the results of previous studies [ 42 , 43 , 45 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…We consistently used the term 'luminal-like' to make the distinction between gene expression based 'luminal type' and IHC-based 'luminal-like' clear. We also agree, that the comparison of different cohorts bears the risk of drawing unjustified parallels and should be done very carefully, as pointed out in our discussion section [5]. The patient selection was similar in Milano and in our institution: both centers are referral-centers for breast cancer patients and both data sets comprised all patients who had undergone surgery for early breast cancer [6].…”
mentioning
confidence: 55%
“…26 For the present time, there is general agreement that cut-off values for high and low proliferation should be defined for each institution individually. [27][28][29] In our experience, the proliferation index varies between 5 and 15% in the majority of prostate carcinomas and hardly ever exceeds 25%. Given this rather small range, the cut-off for high and low proliferation would be around 10%.…”
Section: Proliferation Index Ki-67mentioning
confidence: 65%